Diagnosis, Phenotype, and Molecular Genetics of Congenital Analbuminemia - Minchiotti, Lorenzo; Caridi, Gianluca; Campagnoli, Monica; Lugani, Francesca; Galliano, Monica; Kragh-Hansen, Ulrich (Frontiers in Genetics, 2019)
Congenital analbuminemia (CAA) is an inherited, autosomal recessive disorder with an incidence of 1:1,000,000 live birth. Affected individuals have a strongly decreased concentration, or complete absence, of serum albumin. The trait is usually detected by serum protein electrophoresis and immunochemistry techniques. However, due to the existence of other conditions in which the albumin concentrations are very low or null, analysis of the albumin (ALB) gene is necessary for the molecular diagnosis. CAA can lead to serious consequences in the prenatal period, because it can cause miscarriages and preterm birth, which often is due to oligohydramnios and placental abnormalities. Neonatally and in early childhood the trait is a risk factor that can lead to death, mainly from fluid retention and infections in the lower respiratory tract. By contrast, CAA is better tolerated in adulthood. Clinically, in addition to the low level of albumin, the patients almost always have hyperlipidemia, but they usually also have mild oedema, reduced blood pressure and fatigue. The fairly mild symptoms in adulthood are due to compensatory increment of other plasma proteins. The condition is rare; clinically, only about 90 cases have been detected worldwide. Among these, 53 have been studied by sequence analysis of the ALB gene, allowing the identification of 27 different loss of function (LoF) pathogenic variants. These include a variant in the start codon, frame-shift/insertions, frame-shift/deletions, nonsense variants, and variants affecting splicing. Most are unique, peculiar for each affected family, but one, a frame-shift deletion called Kayseri, has been found to cause about one third of the known cases allowing to presume a founder effect. This review provides an overview of the literature about CAA, about supportive and additional physiological and pharmacological information obtained from albumin-deficient mouse and rat models and a complete and up-to-date dataset of the pathogenic variants identified in the ALB gene.